Beta-2 agonists and exercise performance in humans - Collomp, K.; le Panse, B.; Candaud, R.; Lecoq, A.-M.; de Ceaurriz, J. (Science & Sports, 2010)
Due to fears of doping effects, the World Anti-Doping Agency has put certain restrictions on the use of the pharmacological class of beta-2 agonists. In 2010, all beta-agonists are prohibited except salbutamol and salmeterol by inhalation, which require a declaration of use in accordance with the international standard for therapeutic use exemptions.